Neuromuscular Training Improves Lower Extremity Biomechanics Associated with Knee Injury during Landing in 11–13 Year Old Female Netball Athletes: A Randomized Control Study - Hopper, Amanda J.; Haff, Erin E.; Joyce, Christopher; Lloyd, Rhodri S.; Haff, G. Gregory (Frontiers in Physiology, 2017)
The purpose of this study was to examine the effects of a neuromuscular training (NMT) program on lower-extremity biomechanics in youth female netball athletes. The hypothesis was that significant improvements would be found in landing biomechanics of the lower-extremities, commonly associated with anterior cruciate ligament (ACL) injury, following NMT. Twenty-three athletes (age = 12.2 ± 0.9 yrs; height = 1.63 ± 0.08 m; mass = 51.8 ± 8.5 kg) completed two testing sessions separated by seven-weeks and were randomly assigned to either a experimental or control group. Thirteen athletes underwent six-weeks of NMT, while the remaining ten served as controls and continued their regular netball training. Three-dimensional lower-extremity kinematics and vertical ground reaction force (VGRF) were measured during two landing tasks, a drop vertical jump and a double leg broad jump with a single leg landing. The experimental group significantly increased bilateral knee marker distance during the bilateral landing task at maximum knee-flexion range of motion. Knee internal rotation angle during the unilateral landing task at maximum knee flexion-extension range of motion was significantly reduced (p ≤ 0.05, g > 1.00). The experimental group showed large, significant decreases in peak vertical ground reaction force in both landing tasks (p ≤ 0.05, g > -1.30). Control participants did not demonstrate any significant pre-to-post test changes in response to the six-week study period. Results of the study affirm the hypothesis that a six-week NMT program can enhance landing biomechanics associated with ACL injury in 11-13 year old female netball athletes.